2021
DOI: 10.3389/froh.2021.676643
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Stress-Response Pathways and Therapeutic Resistance in Head and Neck Cancer

Abstract: Head and neck cancer is the sixth leading cancer worldwide; head and neck squamous cell carcinoma (HNSCC) accounts for more than 90% of incident cases. In the US, cases of HNSCC associated with human papillomavirus (HPV) have been growing in proportion amongst a younger demographic with superior outcomes to the same treatments, relative to cases associated with tobacco. Yet failures to improve the long-term prognosis of advanced HNSCC over the last three decades persist in part due to intrinsic and acquired me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…One study reported that prolonged treatment with CTX promoted p27 Kip1 -mediated G1 arrest with the induction of autophagy [ 58 ]. The activation of autophagy has been shown to have opposing roles with respect to radiation response with some reports showing autophagy to be a radiosensitizer [ 59 , 60 ], while others show it plays a role in radioresistance [ 61 ]. Interestingly, a recent study found that EGFR expression and RT response depended on the human papilloma virus (HPV) status of the tumors [ 62 ].…”
Section: Egfr Alterations and Radiation Responsementioning
confidence: 99%
“…One study reported that prolonged treatment with CTX promoted p27 Kip1 -mediated G1 arrest with the induction of autophagy [ 58 ]. The activation of autophagy has been shown to have opposing roles with respect to radiation response with some reports showing autophagy to be a radiosensitizer [ 59 , 60 ], while others show it plays a role in radioresistance [ 61 ]. Interestingly, a recent study found that EGFR expression and RT response depended on the human papilloma virus (HPV) status of the tumors [ 62 ].…”
Section: Egfr Alterations and Radiation Responsementioning
confidence: 99%
“…More than 90% of oral cancer is classified as oral squamous cell carcinoma (OSCC), with 377,713 new cases and 177,757 deaths worldwide in 2020. 1 , 2 Together with surgery, chemotherapy in combination with radiotherapy for OSCC have been developed in the past couple of decades. Cisplatin (CDDP), the most classic platinum‐based cytotoxic agent adapted to various types of malignancies, remains a pivotally important chemotherapeutic drug for OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer is the sixth most commonly diagnosed cancer worldwide, and oral cancer is the most frequent tumor of the head and neck region. More than 90% of oral cancer is classified as oral squamous cell carcinoma (OSCC), with 377,713 new cases and 177,757 deaths worldwide in 2020 1,2 . Together with surgery, chemotherapy in combination with radiotherapy for OSCC have been developed in the past couple of decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant conditions in the orofacial region constitute an important group of human diseases with an estimated prevalence of about 5-8% of all malignancies worldwide, and squamous cell carcinoma accounts for up to 90% of all these lesions in the head and neck region. [1][2][3] Orofacial squamous cell carcinoma (OfSCC) originates from the mucosal epithelium in the aerodigestive tract (oral cavity, pharynx, and sinuses) [4] and keratinocytes in the spinous layer of the epidermis (skin). [5] Generally, OfSCC tends to affect more males than females by twofold to fourfold, with the median age of diagnosis being around 60 years, though, the incidence of OfSCC in persons under the age of 45 years is increasing.…”
Section: Introductionmentioning
confidence: 99%